Estudio de Prefactibilidad Para la Producción y Comercialización de quesadillas con contenido de fruta (2021)
The main objective of the research is to carry out a pre-feasibility study on the production and commercialization of quesadillas with fruit content, the main theoretical contributions of this research are based on the theories developed by Rodríguez (2001), Drucker (2004) and Schumpeter (1911), which expose topics such as innovation, economic development and feasibility theories that are used to generate a guide and direct the project towards success, achieving the best results and the growth necessary to industrialize the business and reach the creation of a company. (Soluciones Queseras SAS). Within the types of existing methodologies, this research is classified within the descriptive type since it is responsible for describing factors in the environment, in addition, it provides a quantitative approach based on data collection by designing a transactional experimental research model, where the Results establish whether the project is viable in each of the studies carried out (market, technical, organizational and financial).